A Cost-Benefit Framework for Analyzing the Economic and Fiscal Impacts of State-Level Immigration Policies - Karoly, Lynn A. (RAND Corporation, 2016)
This report uses a cost-benefit framework to classify the potential impacts of specific state-level immigration policies, identifying the potential domains of impact and how different stakeholders in the public and private sectors would be affected; assembles empirical evidence of the expected impacts; and assesses the rigor and relevance of existing studies of the fiscal and economic impacts of specific state-level immigration policy actions.